Factors Affecting the Welfare Level of Tobacco Farmers in Situbondo Regency, East Java - Dita Atasa; Dona Wahyuning Laily; Ida Syamsu Roidah; Ika Purnamasari (Future Science, 2022)
This study aims to determine the effect of income, last education, land area, number of children, and length of work. This research is a quantitative study with primary data from questionnaires taken from samples of tobacco farmers in Situbondo Regency. The number of respondents from tobacco farmers in Situbondo Regency used as a sample is 250. The results of the data from the questionnaire will be processed using a logistic regression analysis tool which is then processed using SPSS. The results of these tests, the results showed that the income variable had a significant negative effect on the welfare level of tobacco farmers with an odd ratio value of Exp (B) of 0.359. The education level variable has no significant positive effect with the odd ratio value of Exp (B) of 1.471. The variable area of ??land has no significant positive effect with the odd ratio value of Exp (B) of 1.951. The variable number of children has a significant negative effect with the odd ratio value of Exp (B) of 0.202. The variable length of work did not have a significant negative effect with the odd ratio value of Exp (B) of 0.729. The value of Nagelkerke's R Square is 0.383, which means that the probability of the welfare level of tobacco farmers is influenced by the independent variables of income, education level, land area, number of children, and length of work of 38.3%, while the remaining 61.7% is explained by the variable other outside the research model.